Ben Quilty at the Saatchi Gallery … things just got interesting - Messham-Muir, Kit (The Conversation Media Group, 2014)
Ben Quilty is the first Australian artist to hold a solo show at the Saatchi Gallery in London. Opening last Friday and running until August 3, the exhibition is a big deal for Quilty, naturally, but also for art in the southeastern corner of the globe. Since the Gallery opened in 1985, it has hosted solo exhibitions by major figures of international contemporary art, such as Jeff Koons (1987), Damian Hirst (1992) and Tracey Emin (2000). A solo show at the Saatchi doesn’t so much launch the careers of major contemporary artists; it means an artist has already entered orbit.